126k views
2 votes
Find the solution of this system of equations
-6y=-50-4x
5x-6y=-49

User Ohjeah
by
5.8k points

2 Answers

5 votes

Answer:

1,9

Explanation:

User Frum
by
5.4k points
6 votes

Answer:


(1,\ 9)

Explanation:

Rewrite the first equation


-6y=-50-4x\\\\4x-6y=-50

Now we have the following system of equations


4x-6y=-50\\5x-6y=-49

To solve the system of equations multiply the first equation by -1 and add it to the second equation


-1*4x-(-1)*6y=-50*(-1)\\\\-4x+ 6y=50


-4x+ 6y=50

+


5x-6y=-49

-----------------------------------


x + 0 =1\\\\x=1

Now substitute the value of x in any of the two equations and solve for y


5(1)-6y=-49


5-6y=-49


-6y=-49-5


-6y=-54


y=(54)/(6)


y=9

The solution is:


(1,\ 9)

User Haseman
by
6.0k points